A NICE perspective on computable biomedical knowledge. Issue 2 (28th July 2020) - Mitchell, Andrew
Abstract : Introduction: The National Institute for Health and Care Excellence (NICE) plays a central role in the NHS. We distill knowledge of best practice from the best available sources of evidence and share this across the health and care system, typically in the form of recommendations. We want to ensure that this knowledge is shared in a form that supports improved decision making by professionals working together with patients, leading to improved outcomes. Understanding the role of computable knowledge in the context of a learning health system is therefore of deep interest to NICE. Methods: The Agency for Healthcare Research and Quality (AHRQ) 4 levels of knowledge have been used as a framework to review current NICE products and services and envisage how they may need to evolve. Discussion: NICE is mostly still at level 1 of the AHRQ knowledge hierarchy but aspires to work towards structured and computable products. The NHS Long Term Plan makes clear that the wider health and care system is seeking to drive up interoperability with standards for data exchange at the heart of this. NICE Connect is the name given to NICE's ambition to change in order to keep pace with changing technologies, advances in guideline development and analytical methods and the shifting needs of the system, and to ensure that it can sustainably and efficiently manage its portfolio of guidance. It is seen as crucial that NICE Connect and the wider Mobilising Computable Biomedical Knowledge (MCBK) agenda align for either of them to truly succeed.